2016
DOI: 10.1016/j.jpeds.2016.08.093
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Utilization and Need for Tympanostomy Tubes across England and New England

Abstract: Objectives To assess rates of tube insertions for otitis media with effusion (OME) with estimates of need. Study Design This cross-sectional analysis used all-payer claims to calculate rates of tube insertions for insured children age 2 to 8 years (2007–2010) across pediatric surgical areas (PSA) for Northern New England (NNE; Maine, Vermont, and New Hampshire) and the English National Health Service Primary Care Trusts (PCT). These rates were compared to expected rates estimated using a Monte Carlo simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…However, there was no difference in the amount of hearing loss at age 5 for children following centralization of services with approximately 50% of children having abnormal middle ear status . Previous studies have suggested that grommet use for children varies geographically with an 8.5‐fold variation across local authorities in England over the period 2011‐2012. We are not aware of any studies that have examined centre‐level variation in treatment or outcomes for hearing in children with cleft lip and palate.…”
Section: Introductionmentioning
confidence: 90%
“…However, there was no difference in the amount of hearing loss at age 5 for children following centralization of services with approximately 50% of children having abnormal middle ear status . Previous studies have suggested that grommet use for children varies geographically with an 8.5‐fold variation across local authorities in England over the period 2011‐2012. We are not aware of any studies that have examined centre‐level variation in treatment or outcomes for hearing in children with cleft lip and palate.…”
Section: Introductionmentioning
confidence: 90%
“…The comparatively high rate of tympanostomy tube insertion in our cohort has several possible explanations. First, the previous reports by Cullen et al (2009) and Parker et al (2016) may underestimate the incidence of tympanostomy tube insertion in children before school-age, since insertion rate declines with age. Indeed, a study of tympanostomy tube insertion in Calgary, Canada, demonstrated that insertion rate dropped from 54 per 1000 person-years between 1 and 2 years of age to just 5 per 1000 person-years between 5 and 15 years of age (Desai et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…Tympanostomy tube insertion for recurrent or chronic otitis media with effusion is the most common pediatric procedure in the United States, accounting for 20% of pediatric ambulatory surgeries (Cullen et al, 2009). Although regional rates of tympanostomy tube insertion are highly variable (Kogan et al, 2000; Haapkylä et al, 2006; Parker et al, 2016), the 2006 National Survey of Ambulatory Surgery reported a rate of 11 per 1000 person-years in children younger than 15 years of age (Cullen et al, 2009). Additionally, a recent study of children aged 2 to 8 years in Maine, Vermont, and New Hampshire reported a range of 4 to 13 tympanostomy tube insertions per 1000 person-years (Parker et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The answer to this question might at first seem simple-recurrent infection, chronic OME, or structural changes of the tympanic membrane-but the nuances of articulating indications in clear, nonambiguous, evidence-based recommendations were not fulfilled until 2013 when the American Academy of Otolaryngology-Head and Neck Surgery Foundation (AAO-HNSF) published the first national CPG on tympanostomy tubes. 4 Prior to this, several studies questioned the need for tube insertion, 3,11,12 leading The Joint Commission and the American Medical Association to include tympanostomy tubes in 2012 on its list of 5 clinical areas of potential overuse. 13 Current best evidence.…”
Section: What Are the Appropriate Indications For Tympanostomy Tubes?mentioning
confidence: 99%